1969
DOI: 10.5254/1.3539243
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Calibration for Gel Permeation Chromatography

Abstract: Gel permeation chromatography is one of the most powerful techniques for characterizing the polydispersity of polymeric materials. A versatile commercial apparatus has been used successfully in numerous laboratories on various problems of molecular weight distributions. But one of the difficulties still unsolved is the problem of calibration, i.e., the relation between elution volume and molecular weight. Some authors have assumed that retention time depends on the contour length of the molecular chain. Others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…The peak retention time of these polymers was then used to calibrate the system to afford both a SEC calibration plot (see Supporting information) and a Universal calibration (Fig. 3) by plotting log(M[η]) versus retention time [34].
Fig. 3Calibration of Agilent PolarGel columns with linear PNIPAM polymers.
…”
Section: Resultsmentioning
confidence: 99%
“…The peak retention time of these polymers was then used to calibrate the system to afford both a SEC calibration plot (see Supporting information) and a Universal calibration (Fig. 3) by plotting log(M[η]) versus retention time [34].
Fig. 3Calibration of Agilent PolarGel columns with linear PNIPAM polymers.
…”
Section: Resultsmentioning
confidence: 99%
“…[1] Later experiments with PS-DVB confirmed, also, the validity of the u.c. The earlier equation was thoroughly tested with crosslinked polystyrene-divynilbenzene (PS-DVB) gels for homopolymers and copolymers with linear and branched structures.…”
Section: Introductionmentioning
confidence: 80%
“…[5,28,29] Among them, it deserves to be remarked that the pioneer proposition of Benoit et al [1,30] the u.c. [5,28,29] Among them, it deserves to be remarked that the pioneer proposition of Benoit et al [1,30] the u.c.…”
Section: Universal Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…A more accurate calibration curve may use the plot of log([η]M) versus retention time, where [η] denotes the intrinsic viscosity and M is the weight average relative molecular mass. The term [η]M is proportional to the solute’s hydrodynamic volume, and Benoit et al [17] demonstrated that a number of polymers with different configurations (e.g., linear, comb-branched, star-branched) all conformed to a single plot of log([η]M) versus the elution volume. However, intrinsic viscosity measurement usually requires large quantities of sample, which is very costly for heparin and heparosan oligosaccharides.…”
Section: Resultsmentioning
confidence: 99%